Design, synthesis, and insecticidal activity of novel 1-alkoxy-2-nitroguanidines. Issue 4 (8th January 2018) - Yang, Dongyan; Wan, Chuan; Xiao, Yumei; Che, Chuanliang; Rui, Changhui; Qin, Zhaohai
Abstract : In searching for new insecticidal lead compounds, a series of novel 1-alkoxy-2-nitroguanidine, guadipyr analogues bearing alkoxy groups were designed, synthesized and confirmed by 1 H NMR, 13 C NMR, high-resolution MS and X-ray diffraction. Abstract : In searching for new insecticidal lead compounds, a series of novel 1-alkoxy-2-nitroguanidine, guadipyr analogues bearing alkoxy groups were designed, synthesized and confirmed by 1 H NMR, 13 C NMR, high-resolution mass spectrometry and X-ray diffraction. The primary bioassays showed that most of these compounds exhibited moderate to good insecticidal activity against Myzus persicae and Aphis gossypii . Especially, the precise insecticidal assay showed that compounds4-02, 4-07 and4-08 displayed excellent in vitro activity with IC50 values lower than 10 μg mL −1 to M. persicae which is comparable to guadipyr. On the other hand, the toxicity of compound4-07 and guadipyr against honey bees was much lower than imidacloprid. The results indicated that the flexible chain on the nitrogen atom was the most crucial factor on honey bee toxicity, which existed in both neonicotinoids and guadipyr series.